Mobilizing Biosciences for food and nutritional security in Africa—The case of BecA-ILRI Hub - International Livestock Research Institute (International Livestock Research Institute, 2012)
On 29 February, 2012, Dr. Segenet Kelemu, Director, Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub, was invited to speak at a conference on "Food Security in the 21st Century - Agricultural, Health, Economic, Judicial and Political Perspectives" organized by the Tel Aviv University. During her presentation, Dr. Kelemu highlights the role BecA-ILRI Hub plays in fostering a knowledge-intensive growth approach to tackling food security challenges in Africa.